Optical Evaluation of New Designs of Multifocal Diffractive Corneal Inlays - Diego Montagud-Martínez; Vicente Ferrando; Juan A. Monsoriu; Walter D. Furlan (Journal of Ophthalmology)
Purpose. To assess the imaging properties of two different designs of a new concept of corneal inlays whose working principle is based on diffraction. Methods. The quality of the retinal images provided by Diffractive Corneal Inlays (DCIs) was evaluated theoretically in comparison with Small Aperture Corneal Inlay (SACI). ZEMAX OpticStudio software was employed for the simulations in an eye model with different pupil diameters (3.0 mm and 4.5 mm). The employed merit functions in the analysis were the Modulation Transfer Function (MTF), the area under the MTF (MTFa), and the Point Spread Function (PSF). Comparison was made with the SACI at different defocus conditions. Results. The bifocal nature of the DCIs was demonstrated in a model eye for the first time. It was shown that the intensity of the near focus depends on the radius of the central zone. Retinal image quality of the DCI was equal to or exceeded the SACI in the majority of visual conditions as was demonstrated with simulated images. Conclusions. A new customizable type of corneal inlays has been evaluated using objective numerical simulations. Improvements in imaging of near objects and in light throughput compared with the popular small aperture inlays were demonstrated. These findings open a new technical branch of minimally invasive surgical solutions for the treatment of presbyopia.